Coming of age in recovery: The prevalence and correlates of substance use recovery status among adolescents and emerging adults. - Douglas C Smith; Crystal A Reinhart; Shahana Begum; Janaka Kosgolla; John F Kelly; Brandon B Bergman; Marni Basic (PLoS ONE)
Background and aims To date, no epidemiological survey has estimated the prevalence of adolescents identifying as being in recovery. This is necessary for planning and identifying the needs of youth with current and remitted substance use disorders. This study estimated the prevalence of recovery status in a large statewide epidemiological survey administered between January and March 2020. Participants Participants were high school students in 9th through 12th grades throughout Illinois. Measurements Youth were asked if they were in recovery and if they had resolved problems with substances. Youth who reported recovery and problem resolving dual status (DS), recovery only (RO), and problem resolution only (PRO) were compared to propensity score matched control groups who reported neither status (neither/nor; NN). Outcomes included alcohol use, binge alcohol use, cannabis use, and prescription drug use in the past 30 days. Findings Prevalence estimates were 884 (1.4%) for DS, 1546 (2.5%) for PRO, and 1,811 (2.9%) for RO. Relative to propensity matched control samples, all three groups had significantly lower odds of prescription drug use. The PRO group had lower odds of past month cannabis use. There were no significant differences for either alcohol outcome. Conclusions Prevalence estimates of youth in recovery are slightly lower than those of adults in recovery, and estimates should be replicated. Youth in recovery and those resolving problems have numerous behavioral health needs, and relative to matched controls, have even odds for past 30-day alcohol use. These findings compel us to further define recovery for adolescents and emerging adults to allow for improving treatments and epidemiological research.